Mycobacterium tuberculosis Protein Rv3841 Activates Dendritic Cells and Contributes to a T Helper 1 Immune Response - Seunga Choi; Han-Gyu Choi; Ki-Won Shin; Yong Woo Back; Hye-Soo Park; Jae Hwi Lee; Hwa-Jung Kim (Journal of Immunology Research)
The attenuated vaccine Mycobacterium bovis BCG (Bacille Calmette Guerin) has limited protective efficacy against TB. The development of more effective TB vaccines has focused on the mycobacterial antigens that cause strong T helper 1 (Th1) responses. Mtb protein Rv3841 (bacterioferritin B; BfrB) is known to play a crucial role in the growth of Mtb. Nonetheless, it is unclear whether Rv3841 can induce protective immunity against Mtb. Here, we studied the action of Rv3841 in maturation of dendritic cells (DCs) and its engagement in the development of T-cell immunity. We found that Rv3841 functionally activated DCs by upregulating costimulatory molecules and increased secretion of proinflammatory cytokines. Activation of DCs by Rv3841 was mediated by Toll-like receptor 4 (TLR4), followed by triggering of mitogen-activated protein kinase and nuclear factor-κB signaling pathways. In addition, Rv3841-matured DCs effectively proliferated and polarized Th1 immune response of naïve CD4+ and CD8+ T-cells. Moreover, Rv3841 specifically caused the expansion of CD4+CD44highCD62Llow T-cells from Mtb-infected mice; besides, the T-cells activated by Rv3841-matured DCs inhibited intracellular mycobacterial growth. Our data suggest that Rv3841 induces DC maturation and protective immune responses, a finding that may provide candidate of effective TB vaccines.